2007
DOI: 10.1152/japplphysiol.00477.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in the activation of human skeletal muscle induced by short-term isometric resistance training

Abstract: This study employed longitudinal measures of evoked spinal reflex responses (Hoffman reflex, V wave) to investigate changes in the activation of muscle and to determine if there are "linked" neural adaptations in the motor pathway following isometric resistance training. Twenty healthy, sedentary males were randomly assigned to either the trained (n = 10) or control group (n = 10). The training protocol consisted of 12 sessions of isometric resistance training of the plantar flexor muscles over a 4-wk period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
173
1
6

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 54 publications
23
173
1
6
Order By: Relevance
“…However, resistance training of the tibialis anterior was associated with a 32% increase in MEP amplitude produced by TMS during low-level contractions without changes in M-wave amplitude, indicating a role for spinal, corticospinal neurons, possibly M1 (25). In addition, several other studies showed that adaptations to acute and chronic voluntary and electrical stimulation-evoked muscle contractions, without a skill component, increased volitional drive from supraspinal centers (4, 13, 15, 24, 31, 32) without concomitant changes in H reflex, measured at rest or during mild voluntary contraction (1,10,13,15,23,24,35,38,50,55). However, the interpretation of these studies must be viewed carefully because they do not provide direct evidence for M1's involvement in strength gains and some studies did find increases in H reflex after resistance training (1,4,15,32).…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 96%
See 1 more Smart Citation
“…However, resistance training of the tibialis anterior was associated with a 32% increase in MEP amplitude produced by TMS during low-level contractions without changes in M-wave amplitude, indicating a role for spinal, corticospinal neurons, possibly M1 (25). In addition, several other studies showed that adaptations to acute and chronic voluntary and electrical stimulation-evoked muscle contractions, without a skill component, increased volitional drive from supraspinal centers (4, 13, 15, 24, 31, 32) without concomitant changes in H reflex, measured at rest or during mild voluntary contraction (1,10,13,15,23,24,35,38,50,55). However, the interpretation of these studies must be viewed carefully because they do not provide direct evidence for M1's involvement in strength gains and some studies did find increases in H reflex after resistance training (1,4,15,32).…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 96%
“…We did not test for any spinal effects. Considering the inconsistent results from TMS (9,25,30) and peripheral nerve stimulation studies (1,4,13,15,23,24,32,35,38), a role for segmental effects cannot be dismissed. We intentionally designed the study to consist of only 10 sessions so that the nature of adaptation would primarily be neuronal (9); it is still possible that a portion of the strength gains was due to muscle hypertrophy.…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 99%
“…Regarding the facilitatory neuromodulative effects of muscle training, it could be demonstrated in several studies that even short-term muscle training increases the excitability in supraspinal and also in spinal centres [17,18]. This is one of the first mechanisms together with adaptations in motor unit recruitment which is involved in the very early changes after starting muscle training [18].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first mechanisms together with adaptations in motor unit recruitment which is involved in the very early changes after starting muscle training [18]. The supraspinal regions involved in EUS control and coordination of pelvic floor muscles including the EUS have been revealed in several imaging studies using PET and fMRI [19].…”
Section: Discussionmentioning
confidence: 99%
“…Practice-related adaptations in the nervous system can include changes in corticospinal excitability (Jensen et al 2005;Perez et al 2007), somatosensory feedback to the motor neurons (Geertsen et al 2007;Zehr 2006), and the output of the motor neuron pool to muscle (Del Balso and Cafarelli 2007;Duchateau et al 2006). The sites of plasticity in the nervous system are specific to the task performed and can differ, for instance, between motor skill training and strength training (Jensen et al 2005;Semmler and Nordstrom 1998).…”
Section: Introductionmentioning
confidence: 99%